PELATIHAN PEMBUATAN HALIA INSTAN UNTUK MENINGKATKAN EKONOMI MASYARAKAT - Asnawi Asnawi; Ronald Fransyaigu; Adi Bejo Suardi; Rapita Aprilia; Ary Kiswanto Kenedi (LPPM dan PM Universitas Samudra, 2021)
Instant gringer for now has a strategic health value where the raw material is very easy to obtain in the community and has properties and benefits in increasing personal immunity. However, it requires the skills of residents to process Halia Instant herbal drinks which can then be produced by considering the availability of raw materials at the farm level. This community service aims to help PKK members of the Simpang Peut Village PKK, Rantau Selamat District in understanding the various kinds of preparations of gringer raw materials and helping PKK members in increasing family economic income. This community service activity is targeted to be able to produce herbal beverage products and to produce knowledge about processing gringer raw materials into finished goods. In the long term, this service program is expected to foster independence for members of the Simpang Peut Village PKK, Rantau Selamat District and are also expected to have self-confidence and the ability to develop a business independently.